Ultra‐Long Van Der Waals CdBr2 Micro/Nanobelts. Issue 10 (1st September 2020) - Wang, Fei; Jia, Lemin; Ding, Ying; Cai, Haihuai; Zheng, Wei; Huang, Feng
Abstract: Recently, 1D van der Waals materials with appealing optoelectronic properties different from 2D layered materials have attracted widespread attention. However, the existing methods are incapable of growing the high‐quality and large‐size 1D van der Waals materials to a certain extent. Here, a new method of organic liquid phase synthesis followed by annealing is proposed, which overcomes the crystal size limitation caused by chemical vapor deposition and successfully synthesizes the high‐quality ultra‐long (millimeter level) van der Waals CdBr2 micro/nanobelts without being limited by substrate matching. The Raman tensor of CdBr2 with extremely high anisotropy is extracted, revealing the structure and physical properties of this van der Waals crystal. What is more, based on this material, the photodetectors with high responsivity are manufactured. Methodologically, compared with current methods, this work indicates the advantages of liquid phase synthesis in growing high‐quality, large‐size 1D van der Waals materials. It is believed that the method proposed in this paper can provide a noble perspective for the study of 1D van der Waals materials and arouse a lot of interest in the field of optoelectronics. Abstract : Large‐size (millimeter level) and high‐quality CdBr2 van der Waals micro/nanobelts are synthesized with a method of organic liquid phase synthesis followed by annealing. The synthetic one‐dimensional CdBr2 van der Waals micro/nanobelts exhibit an ultra‐high Raman scattering anisotropy, based on which a UV photodetector with excellent light response characteristics is integrated.